2013
DOI: 10.1007/s10995-013-1363-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive Childbirth Experiences in US Hospitals: A Mixed Methods Analysis

Abstract: Objective Research on maternity care quality in the U.S. often focuses on avoiding adverse events. Positive birth experiences receive less attention. This analysis used a mixed methods approach to identify factors associated with confidence and positive experiences during birth among a national sample of U.S. mothers. Methods Data are from a nationally representative survey of women who delivered a singleton baby in a U.S. hospital in 2005 (N=1,573). We explored the relationship between confidence, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 40 publications
8
74
0
5
Order By: Relevance
“…A recent integrative review also concluded that maternal self‐efficacy is related to childbirth outcomes and is likely modifiable through specific interventions . Finally, women who responded affirmatively about being confident in labor were more likely to have responded to open‐ended questions with comments about previous pregnancy experiences, positive communication with their maternity care providers, and opportunity for shared decision making . Our findings complement and extend these studies through more detailed discussions with women focusing on the client‐provider relationship and external supports.…”
Section: Discussionsupporting
confidence: 74%
“…A recent integrative review also concluded that maternal self‐efficacy is related to childbirth outcomes and is likely modifiable through specific interventions . Finally, women who responded affirmatively about being confident in labor were more likely to have responded to open‐ended questions with comments about previous pregnancy experiences, positive communication with their maternity care providers, and opportunity for shared decision making . Our findings complement and extend these studies through more detailed discussions with women focusing on the client‐provider relationship and external supports.…”
Section: Discussionsupporting
confidence: 74%
“…Emotional, informational and tangible support have positive effects on a woman's mental and physical well-being during labor, according to a recent review (Iliadou, 2012), and labor support reportedly enhances the birth process and increases satisfaction with childbirth (Attanasio, McPherson, & Kozhimannil, 2014;Aune et al, 2014). In this study we also found that all three kinds of support correlated significantly with a positive birth experience.…”
Section: ) In Previous Studies It Is Important To Note That Althsupporting
confidence: 75%
“…Another key attribute of a woman's confidence for physiologic birth was her belief in her innate ability to birth . In numerous instances, women described confidence in their body's ability or a confidence in their innate ability to give birth (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Women's past experiences with labor and birth were also a prominent attribute of confidence for physiologic birth . Previous experience giving birth reassured women that they were capable, both physically and psychologically, of giving birth again.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation